Determinants of climate change awareness among emerging commercial maize farmers in Limpopo province, South Africa - Tshilowa, Phathutshedzo Fancy; Antwi, Michael Akwasi (Asian Journal of Agriculture and Rural Development, 2025)
Farmers’ awareness of climate change is a crucial starting point for developing effective adaptation strategies and environmental management. A low level of awareness can delay the implementation of adaptation measures, increasing farmers' vulnerability to the adverse effects of climate change. This study employed a deductive approach and a quantitative method to analyze factors associated with climate change awareness among emerging commercial maize farmers in the Limpopo province of South Africa. Primary data were collected from 288 randomly selected farmers using a semi-structured questionnaire. The data were analyzed using a Binary Logistic Regression model in SPSS version 28. The results indicated that education (coef. = 0.347; sig. = 0.060), discussion of climate change within farming organizations (coef. = 1.994; sig. = 0.011), farmers’ belief that climate change negatively impacts farming (coef. = 0.790; sig. = 0.005), and social media usage (coef. = 5.026; sig. = 0.000) were statistically significant factors. The study recommends enhancing climate change education, utilizing social media to disseminate information, and encouraging discussions about climate change among farmers. Additionally, policymakers and the government should allocate sufficient budgets for farmers’ training workshops focused on climate change awareness, adaptation strategies, and environmental management.